Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4236/jbbs.2013.37055
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Diazepam Affect Anxiety-Like and Depression-Like Behavior in Wistar Rats: Possible Interaction with Central GABA Neurotransmission

Abstract: Recent studies have shown the importance of the GABA-ergic transmission in the pathophysiology of anxiety and depressive disorders in humans. Our present study aims to investigate the interaction of melatonin (MEL) with this system by exploring the effects of MEL with or without a facilitator of GABA-ergic neurotransmission, diazepam (DZ) on the levels of depression and anxiety in Wistar rats. For this purpose, different doses of MEL (2, 4 or 16 mg/kg) or DZ (2 mg/kg) are subchronically administered during 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…In addition, exogenous administration of Mel could ameliorate the depressive-like behavior induced by Ni; this neurohormone significantly reduced immobility time in the FST. Consistent with other reports, it was found that Mel produces a variety of anxiolytic-like effects in different tests [ 24 , 37 , 38 ]. Also, Stefanovic et al showed that Mel elicited a real power antidepressant-like effect in the FST [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, exogenous administration of Mel could ameliorate the depressive-like behavior induced by Ni; this neurohormone significantly reduced immobility time in the FST. Consistent with other reports, it was found that Mel produces a variety of anxiolytic-like effects in different tests [ 24 , 37 , 38 ]. Also, Stefanovic et al showed that Mel elicited a real power antidepressant-like effect in the FST [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…This sexual dimorphism suggests the involvement of sexual hormones in the modulation of affective disorders by regulating neurotransmitter synthesis release or actions. In this sense, gonadal hormones contribute to the anatomical or functional characteristics of several neurotransmitter systems such as serotoninergic (5-HT) and gabaergic (GABA) systems that regulate anxiety and depression [83] [84] [85]. Edinger and Frye confirmed that sexual experience is associated with lower levels of anxiety-like behaviour and higher levels of androgen secretion [86].…”
Section: Discussionmentioning
confidence: 99%
“…Edinger and Frye confirmed that sexual experience is associated with lower levels of anxiety-like behaviour and higher levels of androgen secretion [86]. It is known that testosterone elevations were associated with reduced male anxiety [83] [84] [85] [87]. Gonadectomy (GDX) in male rats would increase anxiety-like behaviour, an effect which would be reversed by systemic administration of dihydrotestosterone (DHT).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that daizepam and amnesia or cognitive impairment and antianxiety effect in rodents. [ 14 15 ]…”
Section: Discussionmentioning
confidence: 99%